THEORY OF ATTRIBUTION DAN KEPATUHAN PAJAK DI MASA PANDEMI COVID-19 - Hanina Halimah Sa'diyah; Rosyid Nur Anggara Putra; Muh Rudi Nugroho (Direktorat Jenderal Pajak, 2021)
Tax compliance is an essential dimension in tax revenue collection. It plays a vital role in achieving a 3% fiscal discipline limit by 2023 and Indonesia's economic recovery. This study aims to analyze the factors that influence the compliance behavior of individual taxpayers (WP OP) from internal and external perceptions (Attribution Theory). The internal factors in this study are awareness, perception of justice, religiosity, whereas the external factors are tax service facilities, tax rate levels, technological advances, and COVID-19 education. The population is all WP OP in Yogyakarta City who registered with KPP Pratama Yogyakarta, of which 100 samples were taken using purposive sampling technique. Structural Equation Model (SEM) Partial Least Square (PLS) method was used to analyze the data. This study found that factors in a form of awareness have a significant positive effect on taxpayer compliance, so do religiosity and technological advances. On the other hand, the perception of fairness has no significant effect, tax service facilities, and COVID-19 education have no significant effect on taxpayer compliance. Lastly, the tax rate level negatively impacts taxpayer compliance, albeit insignificant.